Comparison of Rheological, Drug Release, and Mucoadhesive Characteristics upon Storage between Hydrogels with Unmodified or Beta-Glycerophosphate-Crosslinked Chitosan - Emilia Szymańska; Anna Czajkowska-Kośnik; Katarzyna Winnicka (International Journal of Polymer Science, 2018)
The physicochemical characteristics of beta-glycerophosphate-crosslinked chitosan hydrogels were investigated upon long-term storage at ambient, accelerated, and refrigerated conditions and compared to unmodified chitosan formulations. Additionally, the impact of chitosan modification on the ex vivo mucoadhesive performance in contact with porcine vaginal mucosa and on the drug release profile from hydrogels was evaluated. Viscosity and mechanical properties of formulations with unmodified chitosan decreased significantly upon storage regardless of tested conditions as a result of hydrolytic depolymerization. Introduction of ion crosslinker exerted stabilizing effect on physicochemical performance of chitosan hydrogels but only upon storage at refrigerated conditions. Beta-glycerophosphate-modified chitosan formulations preserved organoleptic, rheological behavior, and hydrogel structure up to 3-month storage at 4 ± 2°C. Viscosity variations upon storage influenced markedly mucoadhesive properties and drug release rate from hydrogels.